# find f(x) = –x3 + x2 + 2x + 7, find f(–3), f(0), and f(2)

Wouldn't you just substitute the value of x (-3, or 0, or 2) into the equation and compute?

Can you just show me how to do the first one....my brain is fried at this point

## Yes, you're correct! To find the value of f(x) for a given value of x, you simply substitute that value into the equation and compute the result.

Let's start with f(–3). We have the equation f(x) = –x^3 + x^2 + 2x + 7. To find f(–3), substitute –3 for x in the equation:

f(–3) = –(–3)^3 + (–3)^2 + 2(–3) + 7

Now, let's simplify the equation step by step:

f(–3) = –(–27) + 9 – 6 + 7

= 27 + 9 – 6 + 7

= 40

Therefore, f(–3) = 40.

To find f(0) and f(2), follow the same process. Substitute 0 for x to find f(0), and substitute 2 for x to find f(2).